Hermeneutika Al-Quran (Telaah Pemikiran Shahrur Mengenai Poligami Dan Perlindungananak): Hermeneutics of the Quran (Shahrur's Thoughts on Polygamy and Child Protection) - Ahmad Junaidi (An-Nisa’ Journal of Gender Studies, 2010)
This paper will present Shahrur's ideas in their entirety in an attempt to contribute to the study of specific Quranic verses concerning Islamic law. For Shahrur, the exemplary life of Muhammad (peace be upon him) provides only a model for contemporary Muslims. Muhammad's life is the first variation, not the only one, nor the last. This means that only the Sunnah and traditions of the first community of believers, which the majority of Muslims consider to be the ideal society, still need to be understood in the light of contemporary readings of the Quran, in the light of their intellectual capacities and worldviews. Therefore, contemporary Muslims should read the text in the light of their own worldviews. This is what is meant by hermeneutics in this paper. Meanwhile, Shahrur groups the problem of polygamy in the theory of limits, namely the minimum limit (al-hadd al-adna) and the maximum limit (al-hadd al-a'la) and then Shahrur uses the standard of quantity and quality in studying the problem of polygamy which in the output can be underlined that a person can practice polygamy on the condition that two conditions are met, namely: (1) the second, third wife and must be a widow who has orphans, and (2) must have a sense of worry about not being fair to his children, both his own children and orphans brought by his wives. Shahrur's orientation in his discussion about polygamy certainly has many similarities with the government's efforts in child protection. What is required in polygamy above is in line with the basic principles of child protection contained in Chapter II article 2 of the Child Protection Law. By being oriented towards the protection and care of children in polygamy and supported by the requirements of ability and justice, Shahrur's concept is in accordance with the principles of care above. Tulisan ini akan memaparkan ide-ide Shahrur secara utuh dalam usahanya untuk memberikan kontribusi bagi pemikiran atas ayat-ayat al-Qur'an khusus mengenai hukum Islam. Bagi Shahrur, kehidupan yang dicontohkan Muhammad saw hanya menyediakan sebuah model bagi muslim kontemporer. Kehidupan Muhammad saw adalah variasi pertama, bukan satu-satunya dan bukan yang terakhir. Hal ini berarti bahwa hanya Sunah dan tradisi masyarakat beriman pertama yang dianggap mayoritas muslim sebagai masyarakat ideal, masih perlu dipahami berdasarkan pembacaan kontemporer al-Quran, berdasarkan sinaran kapasitas intelektual dan pandangan dunia mereka, sehingga umat Islam kontemporer hendaknya membaca teks berdasarkan sinaran pandangan dunia mereka sendiri. Inilah yang maksud hermeneutika dalam tulisan ini. Dalam pada itu Shahrur mengelompokkan masalah poligami pada teori limit, yaitu batas minimal (al-hadd al-adna) dan batas maksimal (al-hadd al-a'la) dan selanjutnya Shahrur menggunakan standar kuantitas dan kualitas dalam mengkaji masalah poligami yang pada ujungnya dapat digarisbawahi bahwa seseorang dapat melakukan poligami asalkan memenuhi dua syarat, yaitu: (1) istri kedua, ketiga dan keempat harus janda yang mempunyai anak yatim, dan (2) harus mempunyai rasa khawatir tidak dapat berbuat adil terhadap anak-anaknya, baik anaknya sendiri ataupun anak yatim yang dibawa oleh istri-istrinya. Orientasi Shahrur dalam pembicaraannya tentang poligami tentu memiliki banyak kesamaan dengan upaya pemerintah dalam perlindungan anak. Apa yang dipersyaratkan dalam poligami di atas selaras dengan prinsip dasar perlindungan anak yang terkandung dalam Bab II pasal 2 UU Perlindungan Anak. Dengan berorientasi pada pengayoman dan pengasuhan anak dalam berpoligami dan didukung oleh persyaratan kemampuan dan keadilan, maka konsep Shahrur tersebut sesuai dengan prinsip pengasuhan di atas.